Clinical Pharmacokinetics of Fosfomycin after Continuous Infusion Compared with Intermittent Infusion: a Randomized Crossover Study in Healthy Volunteers - al Jalali, Valentin; Matzneller, Peter; Wulkersdorfer, Beatrix; Chou, Scharon; Bahmany, Soma; Koch, Birgit C. P.; Zeitlinger, Markus (Antimicrobial agents and chemotherapy, 2020)
Continuous infusion (CON) of fosfomycin has been proposed as potentially advantageous in certain clinical scenarios. However, no clinical data on the pharmacokinetics (PK) of fosfomycin after CON are available to date. This study aimed to investigate the PK of fosfomycin after CON and compare it with intermittent infusion (INT) of fosfomycin. A randomized two-way crossover study including 8 healthy male volunteers was performed. Each subject received fosfomycin as INT of 8 g over 30 min every 8 h and, separated by a washout period, as CON of 1 g/h preceded by a loading dose of 8 g over 30 min. Continuous infusion (CON) of fosfomycin has been proposed as potentially advantageous in certain clinical scenarios. However, no clinical data on the pharmacokinetics (PK) of fosfomycin after CON are available to date. This study aimed to investigate the PK of fosfomycin after CON and compare it with intermittent infusion (INT) of fosfomycin. A randomized two-way crossover study including 8 healthy male volunteers was performed. Each subject received fosfomycin as INT of 8 g over 30 min every 8 h and, separated by a washout period, as CON of 1 g/h preceded by a loading dose of 8 g over 30 min. PK sampling was performed for 18 and 24 h in the CON and INT groups, respectively. Fosfomycin was generally well tolerated. However, 2 out of 8 subjects (25%) developed thrombophlebitis at the infusion site following CON, which was prevented in the following subjects with a simultaneous coinfusion of Ringer’s lactate. The steady-state maximum concentration of drug in serum ( C max ) and area under the concentration-time curve from 0 to 24 h at steady state (AUC SS,0–24 ) of fosfomycin after INT were 551.5 ± 67.8 mg/liter and 3,678.5 ± 601.9 h · mg/liter, respectively. CON led to an average steady-state concentration of 183.8 ± 35.9 mg/liter, resulting in a calculated AUC SS,0–24 of 4,411.2 ± 862.4 h · mg/liter, which was 1.2-fold higher than that with INT. CON resulted in a 100% T >MIC (time during which the drug concentration exceeds the MIC) for MICs of ≤128 mg/liter, whereas the % T >MIC for INT was only 44% for an MIC of 128 mg/liter. CON of fosfomycin led to improved PK and PK/pharmacodynamic (PD) determinants in plasma of healthy volunteers. The clinical relevance of these findings remains to be investigated in patients.